THE IMPACT OF FICTIONAL LITERATURE ON THE STUDENT - Rustamov Ilkhom Tursunovich (TADQIQOTLAR.UZ, 2024)
Abstract: This article delves into the significant impact of fictional literature on students. Through an exploration of pertinent academic literature and critical discourse, the research endeavors to elucidate the diverse mechanisms through which engagement with fiction influences students' cognitive, emotional, and social maturation. Employing a qualitative research approach, the study scrutinizes how fictional literature affects students' capacities for critical thinking, empathy, and cultural understanding. The results underscore the substantial contribution of fiction in enhancing students' educational journeys and promoting comprehensive development.